2018
DOI: 10.1039/c7cc09083h
|View full text |Cite
|
Sign up to set email alerts
|

Three-component difluoroalkylation and trifluoromethylthiolation/trifluoromethylselenolation of π-bonds

Abstract: This report describes a new method for three-component difluoroalkylation and trifluoromethylthiolation/trifluoromethylselenolation of π-bonds via air-stable SCF and SeCF reagents as free-radical initiators of ethyl iododifluoroacetate. β-Proton elimination can be overcome effectively in this reaction system, and a broad substrate scope, including alkenes and alkynes, makes this approach practical and attractive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 68 publications
0
30
0
1
Order By: Relevance
“…b) Very recently, Qing disclosed tandem trifluoromethylthiolation/aryl migration of aryl alkynoates to afford a mixtures trifluoromethylthiolated alkenes; Zhu just reported cyanotrifluoromethylthiolation of unactivated dialkyl‐substituted alkynes via intramolecular cyano migration to deliver E ‐olefinic products (Scheme b) . c) Liang described three‐component difluoroalkylation and trifluoromethylthiolation of terminal alkynes to build high stereoselectivity alkenes (Scheme c); A chloro‐trifluoromethylthiolation of terminal alkynes using CF 3 SO 2 Cl as a difunctionalization reagent giving was reported by Zhang (Scheme d) . The vicinal difunctionalization of alkenes and alkynes is particularly important transformations, and can be used to make highly complex molecular architectures.…”
Section: Methodsmentioning
confidence: 99%
“…b) Very recently, Qing disclosed tandem trifluoromethylthiolation/aryl migration of aryl alkynoates to afford a mixtures trifluoromethylthiolated alkenes; Zhu just reported cyanotrifluoromethylthiolation of unactivated dialkyl‐substituted alkynes via intramolecular cyano migration to deliver E ‐olefinic products (Scheme b) . c) Liang described three‐component difluoroalkylation and trifluoromethylthiolation of terminal alkynes to build high stereoselectivity alkenes (Scheme c); A chloro‐trifluoromethylthiolation of terminal alkynes using CF 3 SO 2 Cl as a difunctionalization reagent giving was reported by Zhang (Scheme d) . The vicinal difunctionalization of alkenes and alkynes is particularly important transformations, and can be used to make highly complex molecular architectures.…”
Section: Methodsmentioning
confidence: 99%
“…154b In 2018, the Liang group found that air-stable SCF 3 and SeCF 3 reagents could act as free-radical initiators of ethyl iododifluoroacetate via reduction reaction (Scheme 73). 155 In the presence of air-stable SCF 3 and SeCF 3 reagents, the difluoroalkylation reaction of alkynes with ethyl iododifluoroacetate proceeded smoothly. β-Proton elimination was successfully avoided.…”
Section: Heterodifluoroalkylation With Alkynesmentioning
confidence: 99%
“…The authors developed a three-component difluoroalkylation and trifluoromethylthiolation of styrene derivatives, and ICF 2 CO 2 Et with reagent 1 in the presence of CsF in 1,2-dimethoxyethane (DME) at 100°C, which led to the desired products in yields ranging between 41 and 83% (Scheme 21). 62 However, none of the desired product was obtained in the reaction with aliphatic alkene. The authors also reported a three-component reaction employing alkynes that underwent difluoroalkylation and trifluoromethylthiolation reactions with ICF 2 CO 2 Et and reagent 1, to generate products with high stereoselectivity.…”
Section: Account Synlettmentioning
confidence: 99%